Comparative study of typical asphalt binders in Xinjiang region modified with warm mix additives - Hu, Bangyan; Ai, Xianchen; Feng, Juan (Frontiers in Materials, 2024)
Xinjiang's representative asphalt binders, such as Karamay and Tahe asphalt, lack sufficient research on warm-mix additive modification effects. Given their unique microstructure and molecular composition differences, comprehensive investigations are essential for a nuanced understanding of these binders. This study added Sasobit and Evotherm warm mix additives to Karamay 90# asphalt and Tahe 90# asphalt, respectively. The evaluation of diverse warm mix additives' impact on diverse asphalt binders involved viscosity, softening point, penetration tests, Fourier transform infrared (FTIR) and analysis of saturate, aromatic, resin, and asphaltene (SARA) fractions. Additionally, molecular models of asphalt were constructed using Materials Studio software, based on the SARA test data. Molecular models of Sasobit and Evotherm were also developed, representing organic wax and a cationic quaternary ammonium surfactant, respectively. Conducting molecular dynamics simulations of warm mix additives and two asphalt molecules yielded valuable insights into solubility parameters and the radial distribution function (RDF). This approach enabled a thorough and comparative exploration of the modification mechanisms employed by various warm mix additives on different asphalt types at a molecular scale. The results indicate that, Evotherm excelled in enhancing high-temperature asphalt performance, while Sasobit surpassed it in low-temperature. The viscosity reduction by Sasobit proved more effective for K90, while for T90 asphalt, the trend was reversed with Evotherm exhibiting superior performance. The solubility parameter in MD simulations consistently correlates with asphalt viscosity results. Sasobit showed enhanced compatibility with K90 asphalt, while T90 asphalt demonstrated greater suitability for modification with Evotherm.